Epidemiological and clinical characteristics of patients with monkeypox virus infection in Callao, 2022–2023 - Mori-Llontop, Laura Melissa (2025)
Introduction. In 2022, the monkeypox virus (mpox) caused a pandemic that particularly affected men who have sex with men (MSM), with people living with HIV/AIDS (PLWHA) being more vulnerable. Objectives. To describe the epidemiological and clinical-laboratory characteristics of patients diagnosed with mpox, highlighting those with mpox and HIV coinfection (2022-2023). Methods. A multicenter, observational, descriptive study was conducted. One hundred and sixty patients admitted between July 2022 and February 2023 to the Sabogal Network EsSalud in the Callao Region (Peru) with mpox confirmed by polymerase chain reaction (PCR) were included. Descriptive statistics (measures of central tendency and variance) were analyzed using STATA 19.5. The variables were: CD4 count, HIV viral load (VL), antiretroviral therapy (ART), clinical presentation, and length of hospitalization. The protocol was approved by the Ethics Committee of the Alberto Sabogal Sologuren Hospital. Results. Of the 160 patients, the mean age was 32.4±7.2 years, 70.6% were MSM, and 59.4% had HIV coinfection. Of the patients with coinfection, the median CD4 count was 387 cells, median HIV VL 149 copies/mcL, 55% were on ART, 100% had rashes, and 50% had pustules. Of the, ninety-four percent were hospitalized with a mean CD4 count of 277 cells and a mean HIV VL of 149,583.5 copies. Conclusions. Most patients diagnosed with MPOX were young MSM participants, and 60% had HIV coinfection on ART. Of those hospitalized, all had CD4 counts <300 cells and a detectable HIV VL.